The wall of separation : the constitutional politics of church and state - Sorauf, Frank J. (Frank Joseph), 1928-2013 (Princeton, New Jersey : Princeton University Press, 1976)
This is the story of some of the most anguished constitutional controversies of our time, those involving the issue of separation of church and state. Few questions stimulated debate as intense as that over prayer in public schools and public aid to parochial schools. In contrast to previous studies, which have focused on the substance of the issues, Frank J. Sorauf's book concentrates on the judicial process in its social and political context. The author discusses all sixty-seven cases in this area of litigation decided by high American appellate courts from 1951 to 1971. He has interview.
Frontmatter -- Preface -- CONTENTS -- LIST OF TABLES -- I. The Constitution and the Separation -- II. The Legal and Religious Context -- III. The Separationist Groups -- IV. The Separationists in Litigation -- V. Goals and Strategies of the Separationist Groups -- VI. The Plaintiffs -- VII. The Separationist Attorneys -- VIII. The Accommodationist Defendants -- IX. The Judges -- X. The Adversary Cases: Incidence and Outcome -- XI. The Friendly Cases -- XII. The Immediate Impacts -- XIII. The Impact on Policy -- XIV. The Changing Shape of Constitutional Litigation -- XV. Epilogue: 1971 to 1974 -- Appendix I. The Universe of Cases -- Appendix II. Sources -- Appendix III. Definitions and Criteria -- Index
Includes index.
Print version record.
Includes bibliographical references and index.
JSTOR
Keywords: Ecclesiastical law -- United States; Church and state -- United States; Droit ecclésiastique -- États-Unis.; Église et État -- États-Unis.; POLITICAL SCIENCE -- Political Ideologies -- General; LAW -- Constitutional; LAW -- Public; Church and state; Ecclesiastical law; United States